The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1986
DOI: 10.1002/ajim.4700100106
|View full text |Cite
|
Sign up to set email alerts
|

A health examination of railway high‐voltage substation workers exposed to ELF electromagnetic fields

Abstract: This is a cross-sectional survey on the health conditions of railways workers active in 258 interconnection and conversion substations all over Italy. Measurements performed in both kinds of substations operating at 220 kV have shown that maximum levels of the electric field strength and of the magnetic flux density at 50 Hz are of the order of 5 kV/m and 15 microT, respectively. Three subject groups, differently exposed (1, 10, 20 h/week), and an unexposed control group, for a total number of 627 workers, con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

1992
1992
2007
2007

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 13 publications
1
15
0
Order By: Relevance
“…In fact, in the Soviet Union some authors reported cardiologic symptoms such as palpitations and dizziness in subjects exposed to ELF-EMF (Bonnel 1982). Subsequently, other authors (Knave et al 1979; Baroncelli et al 1986) did not confirm these data, but a recent epidemiological study suggests the hypothesis of a possible association between occupational exposure to ELF-EMF and sudden cardiac death (Graham et al 1996;Savitz et al 1999).…”
Section: Introductionmentioning
confidence: 89%
“…In fact, in the Soviet Union some authors reported cardiologic symptoms such as palpitations and dizziness in subjects exposed to ELF-EMF (Bonnel 1982). Subsequently, other authors (Knave et al 1979; Baroncelli et al 1986) did not confirm these data, but a recent epidemiological study suggests the hypothesis of a possible association between occupational exposure to ELF-EMF and sudden cardiac death (Graham et al 1996;Savitz et al 1999).…”
Section: Introductionmentioning
confidence: 89%
“…Checcucci (26) found no effect on the cardiovascular system of 1200 workers at high-voltage railway substations (1-4.6 kV/m and 4-15 µT). In a health survey of 627 railway high-voltage substation workers, Baroncelli et al (3) found no difference in electrocardiographic findings between exposed and control groups.…”
Section: Long-term Effects On Cardiovascular Functionmentioning
confidence: 96%
“…Medical examinations of 379 workers in electrical substations in Italy revealed no adverse clinical sym ptoms relative to a control group of 133 workers (7). Laboratory studies on humans exposed to ELF magnetic fields have also failed to reveal any adverse physiological or psychological symptoms in the exposed subjects.…”
Section: Laboratory Investigationsmentioning
confidence: 97%